No Children Should Be Left Behind During COVID-19 Pandemic: Description, Potential Reach, and Participants' Perspectives of a Project Through Radio and Letters to Promote Self-Regulatory Competences in Elementary School - Cunha, Jennifer; Silva, Cátia; Guimarães, Ana; Sousa, Patrícia; Vieira, Clara; Lopes, Dulce; Rosário, Pedro (Frontiers in Psychology, 2021)
Around the world, many schools were closed as one of the measures to contain the spread of the COVID-19 pandemic. School closure brought about important challenges to the students’ learning process. This context requires strong self-regulatory competences and agency for autonomous learning. Moreover, online remote learning was the main alternative response to classroom learning, which increased the inequalities between students with and without access to technological resources or for those with low digital literacy. All considered, to level the playing field for students without digital resources, there is an urgent need to promote self-regulatory competences through offline intervention solutions. The current paper describes a project with this purpose, using radio broadcasting and letters to reach elementary students without digital resources. Moreover, potential reach and participants’ perspectives of the project implementation are presented and discussed. The project draws on a prior evidence-based story-tool intervention grounded on a self-regulated learning framework. The original intervention was set previous to the COVID-19 pandemic and was implemented in the classroom context (N = 1103 students). Once the schools had been closed down, the mode of intervention was adapted with the collaboration of the community. Alternative solutions were developed as follows: i) story chapters were read on the radio and students received to their homes a printed script, prompting reflection and suggesting related activities; ii) students were provided with the story-tool to read autonomously and received letters from the main characters of the story which included, for example, suggestions for activities and reflection. These two alternative modes of intervention delivery potentially reached 394 elementary students, including students with digital resources. Interviews conducted with a group of students were provided information about the positive aspects of these two modes of intervention delivery, perceived learning (e.g., planning), constraints, and suggestions to improve the project. The current work is likely to merit attention from researchers and educational practitioners, given the need to use offline alternatives to provide support for students without digital resources to engage in autonomous learning during the pandemic period. This project may also be used as an alternative or a complementary solution to online modality.